Technology of Quantum Devices - Razeghi, Manijeh; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Technology of Quantum Devices covers a wide range of topics in solid state physics, presenting an overview of areas like photonics, semiconductors and crystals. The book presents the most up-to-date developments in semiconductor physics and nano-engineering, with a particular focus on specific areas like compound semiconductors, crystal growth techniques and silicon and compound semiconductor device technology. The book uses a thorough set of sample problems, including the use of clear and detailed mathematical derivations in order to present clear, concise explanations for readers. Other important areas covered include semiconductor lasers, quantum tunneling transport, quantum well intersubband photodetectors and quantum dot photodetectors. Technology of Quantum Devices is a must-read for engineers, researchers and students working in the fields of electrical engineering, materials science or solid state electronic devices.
Single Crystal Growth -- Semiconductor Device Technology -- Semiconductor Device Processing -- Semiconductor and Metal-Semiconductor Junctions -- Transistors -- Semiconductor Lasers -- Quantum Cascade Lasers -- Photodetectors: General Concepts -- Photon Detectors -- Type-II InAs/GaSb Superlattice Photon Detectors -- Quantum Dot Infrared Photodetectors -- Single-Photon Avalanche Photodiodes -- Terahertz Device Technology.
Keywords: Electronics; Nanotechnology; Materials Science; Nanotechnology; Electronics and Microelectronics, Instrumentation; Solid State Physics; Spectroscopy and Microscopy